Cosmic ray studies at high southern latitudes with special reference to the daily intensity variation. - Parsons, N R(Neville Ronsley) (1959)
The equipment described in this report was designed for continuous long term recording of cosmic ray intensity at the Australian National Antarctic Research Expedition's Station at Mawson, Antarctica. This equipment was put into operation in 1955. The records obtained will be used in studies of meteorological effects, directional asymmetries, periodic variations, solar flare and magnetic storm effects, world wide fluctuations and possible relationships with other geophysical and solar phenomena. This work forms part of a joint A.N.A.R.E. ~ University of Tasmania project. The development and construction of the equipment was carried out in the Physics Department, University of Tasmania. It is thought that this report will be of interest particularly to those participating in cosmic ray studies during the 1957-58 International Geophysical Year. The manuscript was originally prepared as a description of equipment and operator's handbook to accompany the equipment at Mawson. It is presented with only minor changes in order to avoid further delay in publication and because it is considered that it embodies valuable ideas which would not be apparent in a bare description of the equipment and which are the result of considerable experience in the management, of scientific projects at remote stations.